Solvothermal-Based Lignin Fractionation From Corn Stover: Process Optimization and Product Characteristics - Khongchamnan, Punjarat; Wanmolee, Wanwitoo; Laosiripojana, Navadol; Champreda, Verawat; Suriyachai, Nopparat; Kreetachat, Torpong; Sakulthaew, Chainarong; Chokejaroenrat, Chanat; Imman, Saksit (Frontiers in Chemistry, 2021)
Fractionation of lignocellulosic is a fundamental step in the production of value-added biobased products. This work proposes an initiative to efficiently extract lignin from the corn stover using a single-step solvothermal fractionation in the presence of an acid promoter (H2SO4). The organic solvent mixture used consists of ethyl acetate, ethanol, and water at a ratio of 30: 25:45 (v/v), respectively. H2SO4 was utilized as a promoter to improve the performance and selectivity of lignin removal from the solid phase and to increase the amount of recovered lignin in the organic phase. The optimal conditions for this extraction, based on response surface methodology (RSM), are a temperature of 180°C maintained for 49.1 min at an H2SO4 concentration of 0.08 M. The optimal conditions show an efficient reaction with 98.0% cellulose yield and 75.0% lignin removal corresponding to 72.9% lignin recovery. In addition, the extracted lignin fractions, chemical composition, and structural features were investigated using Fourier transform infrared spectroscopy, thermogravimetric analysis, elemental analysis, and two-dimensional heteronuclear single quantum coherence nuclear magnetic resonance spectroscopy (2D-HSQC NMR). The results indicate that the recovered lignin primarily contains a β-O-4 linking motif based on 2D-HSQC spectra. In addition, new C–C inter-unit linkages (i.e., β-β, and β-5) are not formed in the recovered lignin during H2SO4-catalyzed solvothermal pretreatment. This work facilitates effective valorization of lignin into value-added chemicals and fuels.